FACTORS AFFECTING STUDENTS’ UNDERSTANDING OF DAILY ENGLISH VOCABULARY - Annisa, Rara Nur; Korompot, Chairil Anwar; Farahdiba, Syarifah (JTechLP: Journal of Technology in Language Pedagogy, 2024)
This research aims to find out what factors affect students' understanding of daily English vocabulary, how they acquire vocabulary, the difficulties and convenience in understanding vocabulary, how to deal with problems if they find new vocabulary, and how they solve problems related to English vocabulary. This research applied a descriptive qualitative method. The data collection in this research was conducted by interviewing 7 students at the State University of Makassar as the participants in this research. The results of this research found that there are several pluses such as Google Translate and E-dictionary are the platforms most often used in understanding daily English vocabulary, finding similarities is an effective way according to students when looking for the meaning of new vocabulary. As for the drawbacks, the drawbacks of this research are when students find words that are almost the same but have different meanings. It can be concluded that external factors (because they are English students) are factors that affect students' understanding of daily English vocabulary.